Full Order Observer Based Control of Single-Phase Inverter Both in Standalone and Gridtie Modes - Nagulapati Kiran (Institute of Advanced Engineering and Science, 2016)
In 3-phase systems, the reliability of 3-phase Inverter is not good. In such situations Paralleled Inverter Systems are used. Parallel Inverter operation has a major topic in uninterruptible power system (UPS) applications where the design is focused on the standalone operation, and output stage is typically an inductor-capacitor filter. Most of the standalone inverter systems use a LC filter and proportional-integral (PI) controller in their control loops. When connecting the paralleled inverters to utility grids, the capacitor becomes redundant and thus either a pure inductor or an LCL filter can be used as inverter output stage. Compared with the L filter, the LCL filter is more attractive because it cannot only provide higher harmonics attenuation with same inductance value, but also allow inverter to operate both in standalone and grid-tie modes, which makes it a universal inverter for distributed generation applications. Output of Inverter should always be checked. In this paper, a full order observer for Inverter System is designed and is used for estimation of State Variables of the Inverter System. Two modes are adopted: a) Grid-tie Mode b) Standalone Mode. MATLAB/Simulink is used to verify and validate the proposed idea.